Levels of catastrophizing pain and kinesiophobia in patients with osteoarthritis and their association - Aristea Vitsa; Ioannis Moisoglou; Petros Galanis; Anastasios Merkouris; Evridiki Papastavrou; Pavlos Sarafis (European Journal of Translational Myology)
Aim of the present study was to assess the level of catastrophizing pain and kinesiophobia in patients with osteoarthritis and to investigate the association between catastrophizing pain and kinesiophobia. This follow-up study included 170 osteoarthritis patients undergoing surgery. They completed the Pain Catastrophizing Scale and the Tampa Scale for Kinesiophobia preoperatively (T0) and then postoperatively, at one (T1) and six months (T2). The mean score of catastrophizing pain preoperatively indicates moderate to high level of catastrophic pain. Multivariable linear regression analysis with total score of Pain Catastrophizing Scale preoperatively as the dependent variable found that increased age was associated with increased total score of Pain Catastrophizing Scale. The mean kinesiophobia score preoperatively indicates moderate to high level of kinesiophobia. Multivariable linear regression analysis with total score of the Tampa Scale for Kinesiophobia preoperatively as the dependent variable found that increased age and increased patients’ inability to manage pain (helplessness) were associated with increased total score of the Tampa Scale for Kinesiophobia. Increased age and catastrophizing pain are predictors of kinesiophobia. Surgical interventions tend to reduce both catastrophizing pain and kinesiophobia.